VISION OF THE WORLD MARITIME AXIS OF INDONESIA AS A MARITIME COUNTRY IN ALFRED THAYER MAHAN’S PERSPECTIVE - E.T. PUDJIASTUTI; I.N. PUTRA; A.K. SUSILO (Journal of Defense Resources Management, 2021)
The economic development of Indonesia and the region has an impact on national maritime security. With these conditions, developments and challenges in the maritime aspect, Indonesia has outlined a policy on the vision of the World Maritime Axis. This vision is a consequence of being a maritime nation with an area that is mostly ocean, as is the policy of Alfred Thayer Mahan (A. T. Mahan). The purpose of this paper is to provide an analysis of the relationship between the vision of the World Maritime Axis (WMA) and the concept of maritime strategy from A.T. Mahan so that it can be seen the relevance of this strategy to the development of President Joko Widodo’s World Maritime Axis (WMA) Vision. Based on the results of analysis, the development of the World Maritime Axis (WMA) Vision is relevant to Alfred Thayer Mahan’s maritime strategy. The relevance, among others, is that Indonesia is between two continents in the world, namely the Asian continent and the Australian continent; Indonesia is also the largest archipelagic country in the world with a very wide maritime area; Demographic bonus is a condition where the productive age population is more than the non-productive age; History records that the Indonesian people have long controlled sea shipping lanes with a fairly formidable fleet; The vision and mission of the government of President Joko Widodo have the ambition to make Indonesia the world’s maritime axis.